Determination of specific gas exchange rates in microperforated modified atmosphere packaging: effect of perforation size and gas concentration - Gergő Szabó; Zsuzsanna Horváth-Mezőfi; Lien Le Phuong Nguyen; Stephen Tully; Zoltán Gillay; Christopher Brian Watkins; Tamás Zsom; Géza Hitka (Journal of Agriculture and Food Research, 2025)
The modified atmosphere packaging for minimally processed or fresh-cut horticultural products, such as fruits and vegetables, presents significant challenges for the food industry. Since fruits remain biologically active after harvest, they require packaging materials that allow for proper gas exchange. The optimal packaging solution depends on factors such as the gas exchange area of the packaging film, temperature, package volume, product weight, and the respiration rate of the stored produce. This study investigates the effects of laser-induced microperforations in 65 μm polypropylene plastic films on the gas exchange rates of key gases (CO2, O2, N2). Two different perforation sizes were tested, with perforated areas ranging from 0.017 to 0.041 mm2. Gas exchange rates were calculated using a polynomial function based on the concentration differences of the gases. The distinctive characteristic of the present study is that it refines the results obtained thus far in relation to laser perforations and their dimensions, which can be utilised for industrial applications.